(untitled) - Nguyễn, Huỳnh Công Lý (Can Tho, 2018)
This thesis introduce about Implementing project activities in Tieng Anh 10 and 11: English as a goreign language teachers' challenges and strategies.
Keywords: English language,Tiếng Anh; Study and teaching,Học và dạy học